PENGEMBANGAN PEMASARAN PRODUK BERBASIS DIGITAL MELALUI PEMANFAATAN TEKNOLOGI PADA UMKM KRIPIK SINGKONG - Sulastri, Neneng; Sucynurhaliza, Rany; Rizqiani, Annisa Zahra; Supartika, Ika; Michdhan, Mirna Novia; Lestari, Nadila (LPPM Universitas Bina Bangsa, 2024)
The development of digital technology opens up great opportunities for Micro, Small and Medium Enterprises (MSMEs) to expand markets and increase competitiveness. This research focuses on Cassava Chip MSMEs in Mandalahaji Village, Pacet District, Bandung Regency, to evaluate the implementation of digital marketing strategies and identify challenges and opportunities in digital transformation. The methods used include observation, discussion and training. The research results show that implementing digital strategies—such as website creation, e-commerce, and branding—significantly expands market reach and increases the competitiveness of MSMEs. However, challenges such as limited capital and competition remain. Recommendations include the need for continuous training in digital marketing, infrastructure support from the government, and collaboration between various parties to overcome obstacles and take advantage of digital opportunities